The Relationship Between the Effectiveness of School Principal Leadership in Improving the Quality of Education - Andiani, Anip; Suroso, Suroso (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: The aim of this research is to provide insight and knowledge regarding the effectiveness of school principal leadership in relation to improving the quality of education. Methodology: This research uses a descriptive approach. This research uses questionnaires, interviews and documentation methods. The research subjects were 30 respondents, using population techniques. Data collection uses a questionnaire instrument to collect data on the effectiveness of school principal leadership with efforts to improve the quality of education. The collected research data was analyzed using descriptive statistical analysis techniques. Testing research hypotheses uses correlation analysis. Main Findings: The results of this research found that there is a relationship between the effectiveness of the principal's leadership and efforts to improve the quality of education at the Sudirman Islamic Vocational School Ungaran, this can be seen from the significance value <0.05. The significance value is Sig. (2-tailed) obtained is 0.000. So the better the effectiveness of the school principal's leadership, the better the efforts to improve the quality of education. The strength of the relationship can be seen from the Pearson correlation value of 0.460 which is categorized as having a moderate relationship. Novelty/Originality of this study: This research has the novelty of exploring the important role of principals in stimulating innovation, driving collaboration, and building supportive learning environments to improve the overall quality of students' educational experiences.